Carbon Nanofibers Grown on Carbon Felt as a Reinforced Current Collector for High‐Performance Lithium−Sulfur Batteries. Issue 21 (20th August 2018) - Yan, Xinxiu; Chen, Tao; Wang, Lei; Li, Xiang; Wang, Hao; Deng, Bangwei; Wei, Zhikai; Qu, Meizhen
Abstract: Lithium−sulfur (Li−S) batteries have attracted much attention, owing to their high theoretical energy density. Many studies have focused on improving areal sulfur loading by using carbonaceous current collectors. However, low sulfur utilization and polysulfide diffusion could be more severe. Herein, we introduce a reinforced current collector consisting of carbon felt (CF) decorated with carbon nanofibers (CNFs), prepared by using chemical vapor deposition (CVD). The CF@CNFs skeleton shows a large specific surface area for well‐dispersed active materials, highly conductive network with faster electronic/ionic transport, and a micro‐/mesoporous structure for spatial confinement on polysulfides. As a result, the cells with CF@CNFs current collectors exhibit a high specific capacity, superior cycling stability, and a good rate capacity. This work will provide a promising choice for designing novel current collectors toward high‐performance, high sulfur‐loading Li−S batteries. Abstract : Call in the reinforcements : A reinforced current collector is fabricated by using chemical vapor deposition growth of carbon nanofibers (CNFs) onto a carbon felt (CF) surface. It provides a large specific surface area and excellent conductive network with fast electronic/ionic transport for high‐sulfur‐loading lithium−sulfur batteries.